A Tale of Two Setae: How Morphology and ITS2 Help Delimit a Cryptic Species Complex in Eulophidae (Hymenoptera: Chalcidoidea). Issue 5 (3rd September 2019) - Perry, Ryan K; Heraty, John M
Abstract: The Holarctic species Cirrospilus vittatus Walker, 1838 (Hymenoptera: Eulophidae) is an important parasitoid of lepidopteran, dipteran, coleopteran, and hymenopteran leaf miners. One of the defining characteristics of the species has been its presumed extensive color variation, with individuals ranging from almost completely dark metallic green or blue to completely yellow with no metallic markings. An integrative approach utilizing morphological and molecular data (28S-D2, COI, ITS2) reveals that C. vittatus sensu lato in North America is a species complex comprised of at least four distinct, sometimes sympatric, species that can attack the same host. This species complex emerges as a monophyletic group, separate from Cirrospilus s.s., which we designate Burkseus  gen. n. The species Burkseus vittatus  comb. n. is redefined and has a Holarctic distribution, and B. flavoviridis (Crawford) comb. n . is reinstated from synonymy with B. vittatus . The following combinations are also proposed: B. elongatus (Bouček) comb. n., B. pinicolus (Askew) comb. n., and B. singa (Walker) comb. n. The following species are described as new: Burkseus sigillatus  n. sp. and B. robustus  n. sp. Some of the species are sympatric at several locations, but they remain molecularly and morphologically distinct. The delimitation of these species impacts our ability to assess their potential as biological control candidates against Citrus Leafminer, Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae), and future invasive leaf miner threats.